Web Based Online Nutrition Consultation System (Telenutrition) at the Nutrition Care Center eaching Factory (NCC-TEFA) - Pratama, Mudafiq Riyan; Amareta, Dahlia Indah; Alfiansyah, Gamasiano; Swari, Selvia Juwita (International Journal of Health and Information System, 2024)
The Nutrition Care Center (NCC) is a Politeknik Negeri Jember Teaching Factory (TEFA) that provides nutritional consultation services to clients. NCC aims to provide nutritional services to Polije employees and the wider community. However, NCC does not yet has an online nutrition consultation system that supports services for clients. The aim of this research was to design and implement an online nutrition consultation system (telenutrition) at NCC Politeknik Negeri Jember. The method used was Scrum which has the stages of user stories, product backlog, sprint planning, daily scrum (sprint execution), sprint review, sprint retrospective. Research informants consisted of the Head of NCC and NCC consultants for identifying user needs. The result showed that telenutrition facilitated clients to get services. Meanwhile, telenutrition also facilitated nutritionists to educate and monitor client nutrition. It can be concluded that the system has been designed and is ready to be implemented at NCC.